Method for synthesizing CHA molecular sieve from coal gangue

Through the high-activity crystal core auxiliary method, the problem of large amount of template agent and long crystallization time in the gangue synthesis CHA molecular sieve was solved, and the efficient synthesis of CHA molecular sieve was achieved, which improved the solid yield and synthesis efficiency.

CN119490194APending Publication Date: 2025-02-21DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202311045791.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-17
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The template agent used for gangue synthesis of CHA molecular sieve is large in use, has a long crystallization time, low synthesis efficiency and low solid yield.

Method used

Using the high-activity crystal core auxiliary method, a mixed gel is formed by mixing silicon source, aluminum source, template agent and water. After heating and crystallization, high-activity crystal core is obtained, and then with coal gangue, water, template agent and The alkali metal source is mixed, and the pre-crystallization and crystallization steps are heated to obtain the CHA powder sieve material.

Benefits of technology

It significantly reduces the dosage of template agent, shortens the crystallization time, improves the synthesis rate and yield, and achieves efficient utilization of coal gangue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490194A_ABST
    Figure CN119490194A_ABST
Patent Text Reader

Abstract

The invention discloses a method for synthesizing a CHA molecular sieve from coal gangue, and belongs to the technical field of coal chemical materials. The method comprises the following steps: S1, mixing a silicon source, an aluminum source, a template agent I and water to obtain mixed gel I; s2, heating and crystallizing the mixed gel I in the step S1 under a closed condition to obtain a high-activity crystal nucleus II; s3, mixing the high-activity crystal nucleus II in the step S2 with coal gangue, water, a template agent II and an alkali metal source to obtain gel III; s4, heating and pre-crystallizing the gel III in the step S3 under a closed condition to obtain a pre-crystallized product I; and S5, heating and crystallizing the product I in the step S4 under a closed condition to obtain the CHA powder sieve material. According to the method for synthesizing the CHA molecular sieve from the coal gangue, disclosed by the invention, the CHA molecular sieve product can be rapidly synthesized at high yield by using the low-activity coal gangue as a raw material under the condition of low template agent dosage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coal chemical materials, and in particular relates to a method for synthesizing CHA molecular sieve from coal gangue. Background Art

[0002] The treatment of coal-based solid waste generated by coal mining has become an environmental issue of concern to countries around the world. A large amount of coal gangue will be produced during the mining and washing process of coal mining, especially in countries like my country where coal is the main energy source. The total output of coal gangue in China has exceeded 5 billion tons and is still growing rapidly. At present, my country's utilization of coal gangue is mainly concentrated in low value-added means such as power generation, heating, and as building material additives, with a comprehensive utilization rate of less than 60%. The main components of coal gangue are SiO2 and Al2O3. How to effectively utilize its rich silicon and aluminum elements and utilize them as materials is of great significance for the high value-added utilization of coal gangue.

[0003] As for the utilization of coal gangue, due to its relative inertness, it is often necessary to activate it before use. Its synthetic molecular sieve research is often used to synthesize type A and type X zeolites, etc. There are also some studies that use it as an Al source to synthesize molecular sieves with high silicon-aluminum ratios such as ZSM-5 and SSZ-13. Due to the low activity of coal gangue, in order to accelerate the utilization of coal gangue and improve the synthesis efficiency, auxiliary crystallization methods are often required to promote synthesis, such as microwave assistance, ultrasonic assistance, etc., but its relatively high energy consumption and cannot be applied to large-scale industrial production. Therefore, how to more efficiently promote the synthesis of molecular sieves from coal gangue raw materials is a key issue.

[0004] For the synthesis of CHA zeolite, the commonly used methods are hydrothermal synthesis, crystallization, fluoride ion assistance, and dry gel conversion. Among them, the high-silicon FAU required by the crystallization method needs to go through tedious dealumination steps, and the introduction of fluoride ions will bring serious pollution. Like the dry gel conversion method, it has some limitations in industrial application, so the hydrothermal synthesis method is still a more ideal synthesis method. In addition, the amount of template agent used in the synthesis of CHA zeolite is large and the cost is high. At present, some researchers have developed benzyltrimethylammonium, choline chloride, and tetraethylammonium hydroxide for the synthesis of CHA, but their synthesis phase range is narrow and difficult to adjust, so how to reduce the use of N,N,N-trimethyl-1-adamantylammonium hydroxide and improve the efficiency and yield of hydrothermal synthesis is particularly critical. Summary of the invention

[0005] In view of this, the present invention provides a method for synthesizing CHA molecular sieve from coal gangue, the main purpose of which is to solve the technical problems of large amount of template used, long crystallization time, low synthesis efficiency and low solid yield in synthesizing CHA molecular sieve.

[0006] In one aspect, the present invention provides a method for synthesizing CHA molecular sieve from coal gangue, the method comprising the following steps:

[0007] S1, silicon source, aluminum source, template I and water are mixed to obtain mixed gel I;

[0008] S2, the mixed gel I in step S1 is heated and crystallized I under a closed condition to obtain high-activity crystal nuclei II;

[0009] S3, the high-activity crystal nucleus II in step S2 is mixed with coal gangue, water, template II, and alkali metal source to obtain gel III;

[0010] S4, the gel III in step S3 is heated under a closed condition to pre-crystallize II to obtain a pre-crystallized product I;

[0011] S5. The pre-crystallization product I in step S4 is heated and crystallized III under a closed condition to obtain a CHA powder sieve material.

[0012] Optionally, in step S2, the temperature of the heating crystallization I is 100° C. to 160° C., and the time of the heating crystallization I is 6 h to 20 h.

[0013] Optionally, the temperature of the heating crystallization I is independently selected from any value of 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, or any range between two values;

[0014] The time for the heating crystallization I is independently selected from any value among 6h, 8h, 12h, 14h, 16h, 18h, 20h, or any range between two of them.

[0015] Optionally, in step S4, the temperature of the heating pre-crystallization II is 80° C.-120° C., and the time of the heating pre-crystallization II is 8-12 hours, preferably 10 hours.

[0016] Optionally, the temperature of the heating pre-crystallization II (ie, the low-temperature pre-crystallization nucleation-inducing temperature) is independently selected from any value of 80° C., 90° C., 100° C., 110° C., 120° C., or any range therebetween.

[0017] Optionally, in step S5, the temperature of the heating crystallization III is 160° C. to 200° C., and the time of the heating crystallization III is 5 h to 24 h.

[0018] Optionally, the temperature of the heating crystallization III is independently selected from any value of 160°C, 170°C, 180°C, 190°C, 200°C, or any range between the two;

[0019] The heating time for crystallization III is independently selected from any value among 5h, 8h, 10h, 12h, 16h, 24h or any range between two values.

[0020] Optionally, the crystallization method of the heating crystallization III can be dynamic crystallization or static crystallization, or a combination of the two crystallization methods.

[0021] In the present invention, dynamic crystallization means that the slurry in the crystallization kettle is in a non-static state, and static crystallization means that the slurry in the crystallization kettle is in a static state.

[0022] Optionally, in step S1, the molar ratio of the components in the mixed gel I is SiO2:Al2O3:OSDA:H2O=100:(2-5):(20-30):(2000-3000); wherein OSDA is an organic template.

[0023] Optionally, in the mixed gel I, the molar ratio of the aluminum source to the silicon source is independently selected from any value among 1:20, 1:30, 1:40, 1:50 or any range value between the two.

[0024] Optionally, in the mixed gel I, the molar ratio of the template I to the silicon source is independently selected from any value among 0.2, 0.25, 0.3 or any range value between the two.

[0025] Optionally, in the mixed gel I, the molar ratio of the water to the silicon source is independently selected from any value among 20, 25, 30 or any range value between the two.

[0026] Optionally, the molar ratio of the components in the gel III is SiO2:Al2O3:M2O:OSDA:H2O=100:(0.5-10):(2-20):(3-10):(2000-5000); wherein M is an alkali metal element and OSDA is a template.

[0027] Optionally, in the gel III, the molar ratio of the aluminum source to the silicon source is independently selected from any value among 1:20, 1:30, 1:40, 1:50 or any range value between the two.

[0028] Optionally, in the gel III, the molar ratio of the organic template to the silicon source is independently selected from any value among 0.2, 0.25, 0.3, or any range between the two.

[0029] Optionally, in the gel III, the molar ratio of the water to the silicon source is independently selected from any value among 20, 25, 30 or any range value between the two.

[0030] Optionally, the molar number of the total silicon source in the gel III is calculated based on the SiO2 contained in the external silicon source and the coal gangue raw material.

[0031] Optionally, in step S3, the addition ratio of the high-activity crystal nuclei II to the gel III is 5wt% to 20wt%, based on SiO2 included in the total silicon source in the gel III.

[0032] Optionally, the addition ratio of the high-activity crystal nuclei II in the gel III is independently selected from any value among 5wt%, 10wt%, 15wt%, 20wt% or any range between the two.

[0033] Optionally, in step S3, the coal gangue is raw coal gangue powder and / or dealuminated coal gangue; the particle size of the coal gangue is greater than 200 meshes. Dealuminated coal gangue is preferred.

[0034] Optionally, the preparation method of dealuminated coal gangue in step S3 includes the following steps: the coal gangue is crushed to obtain raw coal gangue powder (>200 mesh), the raw coal gangue powder is calcined and activated to obtain product I, the product I is ball milled to obtain product II, and the product II is acid treated to obtain the dealuminated coal gangue.

[0035] Optionally, the calcination is carried out in air at 750°C for 10 hours; the ball milling is carried out using a planetary ball mill for 6 hours; the acid treatment is carried out using 20wt% hydrochloric acid at 80°C for 3 hours; the product after acid treatment is washed to a pH of ~7.0 to obtain dealuminated coal gangue.

[0036] Optionally, in step S3, the components in the gel III further include an external silicon source, and the external silicon source is selected from at least one of silica sol, silica gel, methyl orthosilicate, ethyl orthosilicate and white carbon black.

[0037] Optionally, in step S1, the silicon source is selected from at least one of silica sol, silica gel, methyl orthosilicate, ethyl orthosilicate and white carbon black.

[0038] Optionally, in step S1, the aluminum source is selected from at least one of aluminum isopropoxide, aluminum oxide, aluminum hydroxide, aluminum chloride, aluminum sulfate and aluminum nitrate.

[0039] Optionally, in step S1, the template agent I is selected from at least one of N,N,N-trimethylphenylammonium hydroxide, N,N,N-dimethylethylammonium bromide, N,N,N-trimethyl-1-adamantylammonium hydroxide and tetraethylammonium hydroxide; in step S3, the template agent II is N,N,N-trimethyl-1-adamantylammonium hydroxide.

[0040] Optionally, in step S3, the alkali metal source is selected from at least one of sodium hydroxide, potassium hydroxide and cesium hydroxide.

[0041] The high-activity crystal nucleus assisted method of the present invention is different from microwave-assisted, ultrasonic-assisted and other external energy-assisted synthesis methods, and is also different from the traditional high-crystallinity seed-assisted method. This amorphous crystal nucleus can promote the further nucleation and growth of the target molecular sieve, greatly improving the synthesis efficiency. At the same time, since it does not need to start from a pure liquid phase component, the amount of template used can be greatly reduced. It is also based on this that the high-activity crystal nucleus assisted method developed by the present invention can be combined with low-activity coal gangue raw materials to achieve a good synthesis effect, improve the resource utilization efficiency of solid waste, and greatly overcome the difficulties of using related low-activity raw materials such as coal gangue for the nucleation of synthetic molecular sieves. The high-activity crystal nucleus assisted method of the present invention has a higher synthesis rate when combined with high-activity coal gangue raw materials.

[0042] In a second aspect, the present invention adopts the above-mentioned synthesis method to prepare a CHA molecular sieve.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] 1) The method for synthesizing CHA molecular sieve from coal gangue with high activity nuclei provided by the present invention provides a way to utilize coal gangue with high added value, and can significantly reduce the amount of template used in the process of synthesizing CHA molecular sieve from coal gangue.

[0045] 2) The method for synthesizing CHA molecular sieves from coal gangue using high-activity crystal nuclei assisted by the present invention can significantly shorten the crystallization time of synthesizing CHA molecular sieves from coal gangue, greatly increase the synthesis rate, and improve the yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 is the X-ray diffraction (XRD) spectrum of sample 1 in Example 1 of the present invention;

[0047] Figure 2 This is a scanning electron microscope (SEM) photograph of sample 1 of Example 1 of the present invention, with a scale of 5 μm;

[0048] Figure 3 The crystallization curves at different times corresponding to the formula of sample 1 in Example 1 of the present invention;

[0049] Figure 4 For sample 1 of Example 1 of the present invention 29 Si MAS NMR spectrum;

[0050] Figure 5 For sample 1 of Example 1 of the present invention 27 Al MAS NMR spectrum;

[0051] Figure 6 This is the XRD spectrum of sample 2 of Example 2 of the present invention;

[0052] Figure 7 This is a SEM photograph of sample 2 of Example 2 of the present invention, with a scale of 10 μm. DETAILED DESCRIPTION

[0053] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.

[0054] Unless otherwise specified, the raw materials in the examples of the present application were purchased from commercial sources and used directly without any special treatment.

[0055] The analysis method in the embodiment of the present invention is as follows:

[0056] The elemental composition was determined using a Philips Magix 2424 X-ray fluorescence analyzer (XRF).

[0057] X-ray powder diffraction phase analysis (XRD) was performed using an X'Pert PRO X-ray diffractometer from PANalytical of the Netherlands, with a Cu target, a Kα radiation source (λ=0.15418 nm), a voltage of 40 kV, and a current of 40 mA.

[0058] Scanning electron microscopy (SEM) tests were performed using a Hitachi SU8020 field emission scanning electron microscope with an accelerating voltage of 2 kV.

[0059] 27 Al MAS NMR and 29 Si MAS NMR experiments were performed on a Bruker Advance III 500 MHz (11.7 T).

[0060] The ball mill used in the embodiments of the present invention is a QM-3SP2 planetary ball mill produced by Nanjing University Instrument Factory.

[0061] Example 1

[0062] The preparation process of dealuminated coal gangue (high activity) is as follows:

[0063] Take a certain amount of crushed coal gangue powder (>200 mesh), roast it in air at 750℃ in a muffle furnace for 10 hours, take it out after roasting, ball mill it with a planetary ball mill for 6 hours, then treat it with 20wt% hydrochloric acid at 80℃ for 3 hours, wash it to pH~7.0, dry it for use, and get dealuminated coal gangue.

[0064] The SiO2 / Al2O3 molar ratio of dealuminated coal gangue tested by XRF is 18.9. The specific composition is shown in Table 1.

[0065] Table 1. Main composition of coal gangue raw materials

[0066] raw material <![CDATA[SiO2 / wt%]]> <![CDATA[Al2O3 / wt%]]> <![CDATA[Fe2O3 / wt%]]> Others / wt% Coal Gangue 51.61 29.99 3.20 15.20 Dealuminated coal gangue 89.13 8.03 0.60 2.24

[0067] The preparation, molar ratio and crystallization conditions of the crystal nucleus solution and synthetic gel are shown in Table 2.

[0068] Nucleus solution: 6.59g silica sol, 0.078g aluminum hydroxide, 7.605g N,N,N-trimethyl-1-adamantyl ammonium hydroxide (25wt%) were dissolved in 8.87g deionized water and stirred for 2 hours. The mixture was transferred into a stainless steel reactor and kept at 120℃ under autogenous pressure for 8 hours before being taken out for use. This is a high-activity nucleus solution.

[0069] Synthetic gel: Take 2.5g of the above-mentioned dealuminated coal gangue, 0.104g of sodium aluminate, 0.976g of sodium hydroxide (10wt%), and 0.628g of N,N,N-trimethyl-1-adamantyl ammonium hydroxide (25wt%) and dissolve them in 12.0g of deionized water, then add 2.897g of the above-mentioned high-activity crystal nucleus solution (calculated according to 10% of SiO2 contained in the total silicon source) and mix and stir for 2h. Transfer the mixture into a stainless steel reactor and pre-crystallize at 120℃ for 10h; continue to heat to 175℃ and rotate and crystallize under autogenous pressure for 5h. After the crystallization is completed, separate the solid and liquid and wash to neutrality, and dry at 100℃ for 10h, which is recorded as sample 1.

[0070] The X-ray powder diffraction pattern (XRD) of sample 1 is as follows: Figure 1 As shown, it is shown that the sample is a molecular sieve with a CHA framework structure.

[0071] The scanning electron microscope (SEM) image of sample 1 is as follows: Figure 2 As shown, the particles of the sample have a typical CHA cubic morphology and a size of about 500nm to 1μm.

[0072] The composition of sample 1 was analyzed by XRF, and the SiO2 / Al2O3 molar ratio was 16.0.

[0073] The crystallization curve of sample 1 is shown in Figure 3 .

[0074] Sample 1 corresponds to 29 Si MAS NMR spectra and 27 Al MAS NMR spectrum is shown in Figure 4 and Figure 5 shown.

[0075] The above spectrum shows that from the coordination of Si and Al in the synthesized product, Si and Al are well integrated into the framework, which also proves that the synthesized molecular sieve has a good coordination structure and no non-framework elements appear.

[0076] Example 2

[0077] Crystal nucleus solution: 1.8g of chromatography column silica gel, 0.078g of aluminum hydroxide, 7.605g of N,N,N-trimethyl-1-adamantyl ammonium hydroxide (25wt%) were dissolved in 8.87g of deionized water and stirred for 2 hours. The above mixture was transferred into a stainless steel reactor and kept at 120°C under autogenous pressure for 10 hours before being taken out for use, which is a high-activity crystal nucleus solution; see Table 2 for details.

[0078] Synthetic gel: Take 0.329g of raw gangue powder (low-activity gangue without pretreatment, components are shown in Table 1), 1.329g of external supplementary chromatography column silica gel, 2.783g of sodium hydroxide (10wt%), 1.479g of N,N,N-trimethyl-1-adamantyl ammonium hydroxide (25wt%), dissolve in 24.006g of deionized water, and then add 1.365g of the above-mentioned high-activity crystal nucleus solution (based on 5wt% of SiO2 contained in the total silicon source) and mix and stir for 2h. The final molar ratio of the feed gel and the crystallization conditions are shown in Table 2. The above mixture is transferred to a stainless steel reactor and pre-crystallized at 110℃ for 10h. Continue to heat to 160℃ and rotate crystallize under autogenous pressure for 24h. After the crystallization is completed, the solid and liquid are separated and washed to neutrality, and dried at 100℃ for 10h, which is recorded as sample 2.

[0079] The X-ray powder diffraction pattern (XRD) of sample 2 is as follows: Figure 6 As shown, it is shown that the sample is a molecular sieve with a CHA framework structure.

[0080] The scanning electron microscope (SEM) image of sample 2 is as follows: Figure 7 As shown, the particles of the sample have a typical CHA cubic morphology and a size of about 1 μm to 2 μm.

[0081] The composition of sample 2 was analyzed by XRF, and the SiO2 / Al2O3 molar ratio was 34.

[0082] Embodiments 3 to 24

[0083] The difference between Examples 3 to 24 and Example 1 is that the crystal core gel ratio, generation temperature, generation time, addition ratio, final feed molar ratio of the synthetic gel, and crystallization conditions are different, as shown in Table 2 for details.

[0084] Table 2. Molar ratio, amount of crystal nucleus solution added, crystallization conditions and sample yield of samples 1 to 24

[0085]

[0086]

[0087]

[0088]

[0089] Note: M2O a : Sodium hydroxide; M2O b :Potassium hydroxide; M2O c : cesium hydroxide;

[0090] SiO2 a : Derived from activated dealuminated coal gangue;

[0091] SiO2 b : Derived from coal gangue and silica gel;

[0092] SiO2 c : Derived from coal gangue and silica sol;

[0093] SiO2 d : Derived from coal gangue and ethyl orthosilicate;

[0094] Al2O3 a : Derived from activated dealuminated coal gangue;

[0095] Al2O3 b : Derived from coal gangue.

[0096] The experimental results of Examples 3 to 24 show that the samples prepared are all CHA zeolites with high crystallinity. The sample morphology is similar to that of the samples in Examples 1 and 2.

[0097] Comparative Example 1

[0098] The difference between Comparative Example 1 and Example 1 is that no high-activity crystal nucleus solution is added to the synthetic gel.

[0099] The raw material ratio, crystallization conditions, etc. of Comparative Example 1 are similar to those of Example 1. Also under the crystallization conditions of 5 h, the synthesized sample is still in an amorphous state, indicating that the assistance of high-activity crystal nucleus solution can accelerate the crystallization of coal gangue raw materials.

[0100] Comparative Example 2

[0101] The difference between Comparative Example 2 and Example 1 is that no high-activity nucleus solution is added to the synthesis gel, but CHA solid seeds (~500nm) with the same SiO2 ratio are used instead.

[0102] The raw material ratio, crystallization conditions, etc. of Comparative Example 2 are similar to those of Example 1. Also under the crystallization conditions of 5 h, the synthesized sample is still in an amorphous state, indicating that the assistance of high-activity crystal nucleus solution can accelerate the crystallization of coal gangue raw materials.

[0103] Comparative Example 3

[0104] The difference between Comparative Example 3 and Example 1 is that no high-activity crystal nucleus solution is added to the synthetic gel, and the crystallization time is extended to 48 hours.

[0105] The raw material ratio, crystallization conditions, etc. of Comparative Example 3 are similar to those of Example 1. As a result, the product did not crystallize, indicating that without the assistance of a high-activity crystal nucleus solution, even if the crystallization time is extended, crystallization cannot be achieved at a low template dosage, indicating that a high-activity crystal nucleus solution can significantly reduce the template dosage.

[0106] Comparative Example 4

[0107] The difference between Comparative Example 4 and Example 1 is that after the high-activity nucleus solution is added to the synthetic gel, no low-temperature guided nucleation (pre-crystallization) process is performed.

[0108] The raw material ratio of Comparative Example 4 is similar to that of Example 1. The yield of the synthesized sample is 68%, and the relative crystallinity is 72% of that of Example 1, both of which are lower than that of Example 1, indicating that the low-temperature guided nucleation step after adding a high-activity nucleus solution can improve the product crystallinity and yield.

[0109] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for synthesizing CHA molecular sieve from coal gangue, characterized in that: The following steps are involved: S1, silicon source, aluminum source, template I and water are mixed to obtain mixed gel I; S2, the mixed gel I in step S1 is heated and crystallized I under a closed condition to obtain high-activity crystal nuclei II; S3, the high-activity crystal nucleus II in step S2 is mixed with coal gangue, water, template II, and alkali metal source to obtain gel III; S4, the gel III in step S3 is heated and pre-crystallized under a closed condition to obtain a pre-crystallized product I; S5. The pre-crystallization product I in step S4 is heated and crystallized III under a closed condition to obtain a CHA powder sieve material.

2. The method for synthesizing CHA molecular sieve from coal gangue according to claim 1, characterized in that: In step S2, the temperature of the heating crystallization I is 100° C. to 160° C., and the time of the heating crystallization I is 6 h to 20 h.

3. The method for synthesizing CHA molecular sieve from coal gangue according to claim 1, characterized in that: In step S4, the temperature of the heating pre-crystallization II is 80° C.-120° C., and the time of the heating pre-crystallization II is 8 h to 12 h.

4. The method for synthesizing CHA molecular sieve from coal gangue according to claim 1, characterized in that: In step S5, the temperature of the heating crystallization III is 160° C. to 200° C., and the time of the heating crystallization III is 5 h to 24 h.

5. The method for synthesizing CHA molecular sieve from coal gangue according to claim 1, characterized in that: In step S1, the molar ratio of the components in the mixed gel I is SiO2:Al2O3:OSDA:H2O=100:(2-5):(20-30):(2000-3000); wherein OSDA is a template.

6. The CHA molecular sieve synthesized from coal gangue according to claim 1, characterized in that: In step S3, the molar ratio of the components in the gel III is SiO2:Al2O3:M2O:OSDA:H2O=100:(0.5-10):(2-20):(3-10):(2000-5000); wherein M is an alkali metal element and OSDA is a template.

7. The method for synthesizing CHA molecular sieve from coal gangue according to claim 1, characterized in that: In step S3, the addition ratio of the high-activity crystal nuclei II to the gel III is 5wt% to 20wt%, based on the SiO2 included in the total silicon source in the gel III.

8. The method for synthesizing CHA molecular sieve from coal gangue according to claim 1, characterized in that: In step S3, the coal gangue is raw coal gangue powder and / or dealuminated coal gangue; the particle size of the coal gangue is greater than 200 meshes.

9. The method for synthesizing CHA molecular sieve from coal gangue according to claim 1, characterized in that: In step S3, the components in the gel III further include an external silicon source, and the external silicon source is selected from at least one of silica sol, silica gel, methyl orthosilicate, ethyl orthosilicate and white carbon black; Preferably, in step S1, the silicon source is selected from at least one of silica sol, silica gel, methyl orthosilicate, ethyl orthosilicate and white carbon black; Preferably, in step S1, the aluminum source is selected from at least one of aluminum isopropoxide, aluminum oxide, aluminum hydroxide, aluminum chloride, aluminum sulfate and aluminum nitrate; Preferably, in step S1, the template agent I is selected from at least one of N,N,N-trimethylphenylammonium hydroxide, N,N,N-dimethylethylammonium bromide, N,N,N-trimethyl-1-adamantylammonium hydroxide and tetraethylammonium hydroxide; in step S3, the template agent II is selected from N,N,N-trimethyl-1-adamantylammonium hydroxide; Preferably, in step S3, the alkali metal source is selected from at least one of sodium hydroxide, potassium hydroxide and cesium hydroxide.

10. A CHA molecular sieve, characterized in that: The CHA molecular sieve is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing CHA molecular sieve by taking gangue as silicon-aluminium sources

    CN105948070A

  • Microwave assisted method for synthesizing CHA molecular sieve from gangue

    CN106365175A

Cited By

  • Synthesis method and application of coal gangue-based in-situ crystallization FCC (fluid catalytic cracking) catalytic material

    CN120714688A

  • Synthesis method and application of coal gangue-based in-situ crystallized FCC catalyst material

    CN120714688B